Computational mapping of redox-switchable metal complexes based on ferrocene derivatives. Issue 49 (30th May 2019) - Lai, Amy; Clifton, Jamie; Diaconescu, Paula L.; Fey, Natalie
Abstract : The properties of redox-switchable metal complexes have been captured with DFT-calculated parameters and processed into a map of chemical space, highlighting the effects of varying metals, donors, linkers and substituents in both accessible ferrocene oxidation states. Abstract : DFT calculations were used to capture the properties of redox-switchable metal complexes relevant to the ring-opening polymerisation of cyclic esters by varying the metals, donors, linkers, and substituents in both accessible ferrocene oxidation states. A map of this chemical space highlights that modifying the ligand architecture and the metal has a larger impact on structural changes than changing the oxidation state of the ferrocene backbone.